KRITIK SANAD - Subhan, Suhuf (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2013)
Criticism is part of the science sanad mustholah very important hadith, which includes being able to determine whether or not a hadith shohih. This science evolved since the days of the prophet companions, much more in the time of Caliph Uthman ibn Affan after the libel Abdullah Ibn Saba in the recent past to his caliphs. Criterion validity isnaad we can see from the definition itself shohih the hadith: hadith isnaad concatenated (to the Prophet of Sallallahu 'alaihi wa sallam) through the narrators are fair and dhobit to the end without any sanad syudzudz (irregularities in matn) and gods (defects).